Fabrication of hierarchically porous TiO2 nanofibers by microemulsion electrospinning and their application as anode material for lithium-ion batteries - Zhang, Jin; Cai, Yibing; Hou, Xuebin; Song, Xiaofei; Lv, Pengfei; Zhou, Huimin; Wei, Qufu (Beilstein Journal of Nanotechnology, 2017)
Titanium dioxide (TiO2) nanofibers have been widely applied in various fields including photocatalysis, energy storage and solar cells due to the advantages of low cost, high abundance and nontoxicity. However, the low conductivity of ions and bulk electrons hinder its rapid development in lithium-ion batteries (LIB). In order to improve the electrochemical performances of TiO2 nanomaterials as anode for LIB, hierarchically porous TiO2 nanofibers with different tetrabutyl titanate (TBT)/paraffin oil ratios were prepared as anode for LIB via a versatile single-nozzle microemulsion electrospinning (ME-ES) method followed by calcining. The experimental results indicated that TiO2 nanofibers with the higher TBT/paraffin oil ratio demonstrated more axially aligned channels and a larger specific surface area. Furthermore, they presented superior lithium-ion storage properties in terms of specific capacity, rate capability and cycling performance compared with solid TiO2 nanofibers for LIB. The initial discharge and charge capacity of porous TiO2 nanofibers with a TBT/paraffin oil ratio of 2.25 reached up to 634.72 and 390.42 mAh·g−1, thus resulting in a coulombic efficiency of 61.51%; and the discharge capacity maintained 264.56 mAh·g−1 after 100 cycles, which was much higher than that of solid TiO2 nanofibers. TiO2 nanofibers with TBT/paraffin oil ratio of 2.25 still obtained a high reversible capacity of 204.53 mAh·g−1 when current density returned back to 40 mA·g−1 after 60 cycles at increasing stepwise current density from 40 mA·g−1 to 800 mA·g−1. Herein, hierarchically porous TiO2 nanofibers have the potential to be applied as anode for lithium-ion batteries in practical applications.
Keywords: anode; hierarchically porous TiO2 nanofibers; lithium-ion batteries; microemulsion electrospinning (ME-ES); multichannel